Influence of bottom water anoxia on nitrogen isotopic ratios and amino acid contributions of recent sediments from small eutrophic Lonar Lake, central India. (5th May 2013) - Menzel, Philip; Gaye, Birgit; Wiesner, Martin G.; Prasad, Sushma; Stebich, Martina; Das, Brijraj Krishna; Anoop, Ambili; Riedel, Nils; Basavaiah, Nathani
Abstract : Lonar Lake is a eutrophic, saline soda lake with permanently anoxic deep water. The high pH and deoxygenation result in very elevated δ 15 N of suspended particulate matter (SPM) and sediments due to denitrification and pH‐related loss of gaseous ammonium. SPM and sinking particles are predominantly aquatic in origin, whereas surface sediments are of mixed terrestrial plant and planktonic source. An indicator of degradation intensity was derived from a principal component analysis of the spectral distribution of amino acids and named Lonar degradation index (LI). A ratio of individual amino acids (Ox : Anox ratio) was additionally used to determine the relative degree of aerobic vs. anaerobic degradation. These two biogeochemical indicators can be used to detect changes in degradation intensity and redox conditions in the geological history, and thus the paleoclimatic interpretation of Lonar sediments. Surface sediments can be divided into three zones: (1) a nearshore, oxic zone of predominantly aquatic organic matter, in which oxidation leads to a strong diagenetic increase of δ 15 N; (2) an alluvial zone with a predominance of isotopically depleted land plant and soil organic matter degraded under oxic conditions; and (3) an anoxic, deep zone, which receives aquatic organic matter and land plant‐derived material transported near the bottom and in which organic matter is well preserved due to anoxic diagenetic conditions.